Identification and validation of myocardial infarction and stroke outcomes at scale in UK Biobank. (2017) - Schnier, Christian; Denaxas, Spiros; Eggo, Rosalind; Patel, Riyaz; Zhang, Qiuli; Woodfield, Rebecca; Flaig, Robin; Hemingway, Harry; Sudlow, Cathie
No abstract available